Hepatitis B prevalence in an endemic area of hepatitis C virus: A population-based study implicated in hepatitis elimination in Thailand - Nawarat Posuwan; Rujipat Wasitthankasem; Napaporn Pimsing; Wijittra Phaengkha; Saranya Ngamnimit; Preeyaporn Vichaiwattana; Sirapa Klinfueng; Maneerat Raksayod; Yong Poovorawan (Journal of Virus Eradication)
Chronic hepatitis B (HBV) and C (HCV) are major health challenges in Thailand, with Phetchabun province, a known HCV-endemic area, being a key target for elimination efforts. This study aimed to assess HBV prevalence and identify associated risk factors in this province. Data was collected from three cross-sectional population studies: (1) adults in 2015 (n = 1,667, age 30–64 years), (2) young adults in 2017 (n = 1,453, age 18–30 years), both from high HCV-endemic districts, and (3) a province-wide study in 2018 (n = 4,769, age 35–64 years). Plasma samples were tested for HBsAg using the ARCHITECT assay. Results showed HBsAg seropositivity in 3.1 % of young adults in high-endemic districts, with significant associations with age, education, injecting drug use, and MSM behavior. Among adults, HBsAg prevalence was 5.9 %, linked to age and family liver disease history. Province-wide, 6.3 % of adults tested positive, with factors like gender and history of blood donation playing significant roles. Notably, age and blood donation were protective factors against HBV in adults. Analysis revealed a moderate HBV prevalence in those born before Thailand Expanded Program on Immunization (EPI) program, while those born after had rates below 1 %. The findings emphasize distinct HBV transmission patterns in different age groups, influenced by social and behavioral shifts. This knowledge is crucial for effective hepatitis elimination strategies in the Phetchabun province and nationwide.